2016
DOI: 10.1177/0265407515590278
|View full text |Cite
|
Sign up to set email alerts
|

Perceived similarity in emotional reaction profiles between the self and a close other as a predictor of emotional well-being

Abstract: Individuals' reaction tendencies in emotional situations may influence their social relationships. In two studies, we examined whether perceived similarity in emotional reaction tendencies between the self and a close other was associated with individuals' emotional well-being. Participants rated how the self and a close other (mother in Study 1; a selfnominated close other in Study 2) would react in various situations. Individuals who perceived greater similarity between the self and the close other reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Our findings are consistent with other studies on couples' perceptions of sad mood, including a daily diary study with the current sample, which showed that both husbands and wives were not accurate in rating their partner's negative mood, but rather relied on their own feelings to make evaluations of their partner's feelings (Kouros & Papp, 2019;Papp et al, 2010;Peters & Overall, 2019). Other studies have shown that perceiving similarity in values, thoughts, and feelings is associated with greater personal adjustment and satisfaction with the relationship (Cheng & Gru ¨hn, 2016;Murray et al, 2002). Thus, one potential explanation of the findings is that assuming similarity may boost feelings of closeness in relationships, particularly when both spouses report lower levels of depressive symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with other studies on couples' perceptions of sad mood, including a daily diary study with the current sample, which showed that both husbands and wives were not accurate in rating their partner's negative mood, but rather relied on their own feelings to make evaluations of their partner's feelings (Kouros & Papp, 2019;Papp et al, 2010;Peters & Overall, 2019). Other studies have shown that perceiving similarity in values, thoughts, and feelings is associated with greater personal adjustment and satisfaction with the relationship (Cheng & Gru ¨hn, 2016;Murray et al, 2002). Thus, one potential explanation of the findings is that assuming similarity may boost feelings of closeness in relationships, particularly when both spouses report lower levels of depressive symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…A similar association was shown regarding the children's perspective toward parents (Cheng & Grühn, 2016). For example, emerging adults who believed that they share similar interests and behaviors with their fathers reported higher relationship quality and were likely to rate their fathers' parental investment higher (Gallup et al, 2016).…”
Section: Introductionsupporting
confidence: 73%
“…First, in only a few studies of perceived self-other similarity have the target others been parents, but those studies suggest that perceived self-parent similarity can have intrapersonal and interpersonal consequences. Among adults, perceived selfmother similarity in emotional reactions to situations was found to positively predict emotional well-being (Cheng & Grühn, 2016). Among adolescents, perceived self-parent value agreement was found to positively predict perceiving their parents as caring and admirable and the self-parent relationship as close (Barni et al, 2011;Knafo & Schwartz, 2012).…”
Section: Communal Motives and Perceived Similaritymentioning
confidence: 87%